Cambodia Puts Fish at the Heart of National Nutrition Strategy - WorldFish (WorldFish, 2025)
In recognition of its essential role in healthy diets, Cambodia has included fish in its newly launched Third National Strategy for Food Security and Nutrition (2024–2028). The strategy, spearheaded by the Council for Agricultural and Rural Development (CARD), aims to boost food security, nutrition outcomes, and resilience nationwide. Speaking at the strategy’s official launch on 10 April 2025, Dr. Ouk Rabun, Senior Minister and Chairman of CARD, acknowledged the crucial role played by WorldFish and other key development partners, highlighting their contributions in shaping the strategic direction for Cambodia’s nutrition and food security future.